Intercultural competences from an intercultural ethical approach in the initial training of professionals in health sciences. An inescapable challenge: Intercultural competences from an intercultural ethical approach in the initial training of professionals in health sciences. An inescapable challenge - Beltrán-Véliz, Juan; Tereucán Angulo, Julio; Alarcón, Ana María; Gálvez-Nieto, José Luis; Vera-Gajardo, Nathaly (Acta Bioethica, 2023)
Chile is a culturally diverse country, and this population must face difficulties related to health. This essay aims to reflect on intercultural competencies from an intercultural ethical approach, in the initial training of professionals in health sciences. The initial training in health sciences shows that health is lacking and decontextualized from the cultural reality. In order to evolve in this area, it is imperative to train professionals in intercultural competencies from an intercultural ethical approach. This will contribute to the recognition and understanding of otherness from their own culture, based on the relationship and exchange of experiences, knowledge, wisdom, among others. This requires intercultural dialogue between professionals and experts belonging to different health systems, in order to co-construct from health and disease. This will allow a timely and adequate response to health demands. It will also provide quality and dignified health care and attention. In effect, it will mitigate inequalities and injustices, while providing a fuller life to people living in a culturally diverse society.